Tax policies and entrepreneurship sustainability in Ondo State, Nigeria - Foluso Olugbenga Aribaba; Rotimi Oladele; Abdul-Lateef Olamide Ahmodu; Saliu Adesina Yusuff (Journal of Global Entrepreneurship Research, 2019)
The study examines the effect of tax policies on the survival of entrepreneurship in Ondo State, Nigeria. The study employed survey research design with the population of 18 local government areas. The study adopted multi-stage sampling techniques to select the sample size of nine local government areas that have duly registered small and medium enterprises (SMEs) under Small and Medium-Scale Enterprise Development Agency of Nigeria (SMEDAN) in Ondo State. Structured questionnaire was administered and returned by the respondents. Data collected was estimated using ordered logistic regression to test the hypotheses formulated. The study revealed that the three explanatory variables (multiple taxation, tax rates, and tax incentives) accounted for 43% of the variability of SMEs sustainability in Ondo State with a p value < 0.05, » = 0.0029. It also revealed that there was a negative significant effect between multiple taxation and sustainability of entrepreneurship; while tax rates and tax incentives have a positive relationship on entrepreneurship sustainability. Based on these findings, the study therefore recommends that for government to truncate unemployment rates that resulted to chronic poverty, banditry, kidnapping, and other social vices in the state, it is imperative that a favorable tax regime shall be provided which will encourage entrepreneurship sustainability and reduces social vises. This will not only enliven existing ones but also inspire the emergence of new ones. Friendly tax regime would engender voluntary compliance amongst the entrepreneurs in the long run with resultant tax yield.
Keywords: 650; Entrepreneurships; Sustainability; Multiple taxation; Tax incentives; Tax rate; Tax policy